Assistancing in developing the Alfina Karim Bakery business, Kendal Regency - Susanto, Dias Andris; Munawar, Muniroh; Cholifah, Nur; Menarianti, Ika; Istiyaningsih, Rumiyatun (Community Empowerment, 2021)
The bread business has been very promising because it is delicious and filling. In addition, bread has many fans of all ages and circles. The problems faced by partners are that entrepreneurial management is not optimal, packaging is less attractive, and there are no labels on the product. The results of this service include partners who were adept at developing variants and decorating bread that suitable for selling to the wider community, being able to market online either through Facebook, Instagram, and other social networks, and having P-IRT. With this service, it is expected to increase product sales.